Characterization of Legionella pneumophila Isolated from Environmental Water and Ashiyu Foot Spa. (11th July 2013) - Tachibana, Masato; Nakamoto, Masaya; Kimura, Yui; Shimizu, Takashi; Watarai, Masahisa
Abstract : Hot springs are the most common infectious source of Legionella pneumophila in Japan. However, little is known about the association between L. pneumophila and environmental waters other than hot springs. In this study, water samples from 22 environmental water sites were surveyed; of the 22 samples, five were L. pneumophila positive (23%). L. pneumophila was mainly isolated from ashiyu foot spas, a type of hot spring for the feet (3/8, 38%). These isolates had genetic loci or genes that encoded the virulence factors of L. pneumophila . Moreover, these isolates showed higher intracellular growth and stronger cytotoxicity compared with the reference strain. These results suggest that ashiyu foot spa can be the original source for L. pneumophila infection.